Kewirausahaan bagi pengungsi asing dan pencari suaka di Pekanbaru pada masa pandemi Covid-19 - Ahmad Jamaan; Muhammad Saeri; Yessi Olivia; Yusnarida Eka Nizmi; Irwan Iskandar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The existence of foreign refugees in Pekanbaru has had an external impact on the social environment of the society in which they are accommodated. Internally, the prohibition of refugees to work formally, it has had the impact of reducing the economic capacity of the refugees itself. Even though, many of them while in their home countries have special professions such as lecturer, lawyer, journalist, and others. Dealing with this reason, in order to strengthen the economy for refugees in Pekanbaru, community service activities are held in the form of introducing and exploring the potential of refugees, socializing the existence of refugees to the society, and entrepreneurship assistance. The activity of entrepreneurship is implemented through three components, namely entrepreneurial motivation, assistance in making products characterized by the country of origin of refugees and the introduction and marketing of these entrepreneurial products. Thus, this community service activities can provide the business independence for refugees in making culinary products and painting crafts. In its implementation, this community service could run well without the presence of refugees and asylum seekers because of absence of permission during Pandemic COVID-19 in Pekanbaru